Flashbulb memory recall in healthy adults – a functional magnetic resonance imaging study. Issue 4 (20th April 2020) - Metternich, B.; Spanhel, K.; Schoendube, A.; Ofer, I.; Geiger, M. J.; Schulze-Bonhage, A.; Mast, H.; Wagner, K.
ABSTRACT: The present study investigated neural activations related to flashbulb memory (FM) recall and examined whether the amygdala and hippocampus are involved in FM recall. 20 healthy adults completed a block design with an FM-condition, where the reception events for a number of potential FM events had to be recalled, and a control condition (FMC) comprising reception events lacking FM characteristics. A definition naming task was used as an implicit baseline. The individual emotional reaction to the FM events (EMO) and self-rated retrieval success were included in the SPM model as modulating parameters. The main contrast of interest were FM > FMC and activations associated with EMO. ROI-analyses on mesiotemporal regions were performed. FM > FMC yielded activations in line with the autobiographical memory network, with mostly left sided-activations. EMO was associated with a more bilateral activation pattern. ROI-analysis revealed activations for EMO in the right amygdala and HATA. FM > FMC was associated with right hippocampal activations. The present findings are compatible with previous research into autobiographical memory, but also show activations for FM recall different from ordinary, not highly emotional autobiographical memories, as EMO is associated with a more bilateral network. Moreover, the amygdala seems to be involved in FM recall.